Transformation of Public Service: A Bibliometric Analysis and A Study of The Population and Civil Registration Office in Palembang City - Mardianto Mardianto; Rahmat Rafinzar; Khairunnas Khairunnas; Alya Syafitri Lubis; Naurah Athaya (Administratio, 2025)
This study aims to see research trends related to the digital transformation of public services globally and combine them with field studies to see the readiness of government agencies in digital public service transformation using the government-to-citizen theory consisting of support, capacity, and value. This study uses a bibliometric analysis method sourced from Scopus as a database and a descriptive qualitative method with data collection techniques carried out by observation, interviews, and documentation. The data used are data from 2019-2024 using Scopus and bibliometric analysis using Vosviewers software. The results of the study show that in terms of support, Disdukcapil has allocated human resources and created several digital innovations such as PACAKELAH TERUS, SIJAGO, and AMPERA CAKEP. Then in terms of capacity, employees are considered competent because they have undergone training, but the technology used is still limited, the waiting room is uncomfortable, and there is a limited budget for the construction of a new building. Then the bibliometric study shows that research on service digitalization, especially in the 2021-2023 period, is growing with a focus on the use of big data, artificial intelligence, collaboration and process automation to improve service effectiveness. The connection is by knowing and understanding this trend, so it is recommended that Disdukcapil can align digitalization strategies with global developments, such as agency preparation in this case meaning strengthening internal capacity and collaborating with other parties to achieve goals.